Postdiagenetic Bacterial Transformation of Nickel and Vanadyl Sedimentary Porphyrins of Organic-Rich Shale Rock (Fore-Sudetic Monocline, Poland) - Stasiuk, Robert; Matlakowska, Renata (Frontiers in Microbiology, 2021)
Nickel and vanadyl porphyrins belong to the so-called fossil geo- or sedimentary porphyrins. They occur in different types of organic matter-rich sediments but mostly occur in crude oils and their source rocks, oil shales, coals, and oil sands. In this study, we aimed to understand the process of bacterial transformation of geoporphyrins occurring in the subsurface shale rock (Fore-Sudetic Monocline, SW Poland). We studied these transformations in rock samples directly obtained from the field; in rock samples treated with bacterial strain isolated from shale rock (strain LM27) in the laboratory; and using synthetic nickel and vanadyl porphyrins treated with LM27. Our results demonstrate the following: (i) cleavage and/or degradation of aliphatic and aromatic substituents of porphyrins; (ii) degradation of porphyrin (tetrapyrrole) ring; (iii) formation of organic compounds containing 1, 2, or 3 pyrrole rings; (iv) formation of nickel- or vanadium-containing organic compounds; and (v) mobilization of nickel and vanadium. Our results also showed that the described bacterial processes change the composition and content of geoporphyrins, composition of extractable organic matter, as well as nickel and vanadium content in shale rock.